On the use of education and training in the treatment of the insane in public lunatic asylums - Lalor, Joseph (Statistical and Social Inquiry Society of Ireland, 1879)
Pinel, who, in 1792, did so much to advance the disuse of mechanical restraint, and the substitution in its stead of moral influence and of kindness, has, with other valuable principles enunciated by him in reference to the treatment of insanity, made the important statement, that thirty years' experience had taught him ?that a striking analogy subsists between the art of educating and teaching the young and that of managing the insane?. Itard, in the early part of the present century, appears to have been the first to have tried the effect of education and training on an imbecile. The subject of his experiment was supposed by him to have been a savage, but Pinel more correctly considered the patient to have been an idiot. What has been done since the experiment of Itard, or what is being done for the education and training of idiots and imbeciles, in England and elsewhere, it is needless for me to say; and such institutions as Earlswood, Clapton, Lancaster, Colchester, Larbert, and others, do not stand in any want of my poor praise.
Read before the Society, August 1878
Keywords: Mental health care; Education; Training; Lunacy; 314.15